New challenges and opportunities for industrial biotechnology - Chen Guo-Qiang (Microbial Cell Factories, 2012)
Abstract Industrial biotechnology has not developed as fast as expected due to some challenges including the emergences of alternative energy sources, especially shale gas, natural gas hydrate (or gas hydrate) and sand oil et al. The weaknesses of microbial or enzymatic processes compared with the chemical processing also make industrial biotech products less competitive with the chemical ones. However, many opportunities are still there if industrial biotech processes can be as similar as the chemical ones. Taking advantages of the molecular biology and synthetic biology methods as well as changing process patterns, we can develop bioprocesses as competitive as chemical ones, these including the minimized cells, open and continuous fermentation processes et al.